PELATIHAN SPSS BAGI MAHASISWA TUGAS AKHIR DI FAKULTAS ILMU ADMINISTRASI UNIVERSITAS BRAWIJAYA - Trisnawati, Trisnawati (MAJU : Indonesian Journal of Community Empowerment, 2025)
This SPSS training aims to improve the data analysis skills of students of the Faculty of Administrative Sciences who are preparing their final projects. The training was carried out in the form of an intensive workshop for five months with a combination of theory and practice sessions. The results of the training showed a significant improvement in students' data analysis skills, which had a positive impact on the quality of their final project. The evaluation showed high participant satisfaction and the success of most participants in the practical exam. This training is expected to continue to be held to support the development of student competencies.